SHORT-TERM ANNUAL VARIATIONS OF RADON CONCENTRATION IN WORKPLACES: SOME RESULTS IN A RESEARCH INSTITUTE. Issue 2 (2nd November 2020) - Venoso, G; Ampollini, M; Antignani, S; Caprio, M; Carpentieri, C; Di Carlo, C; Bochicchio, F
Abstract: Many international and national regulations on radon in workplaces, including the 2013/59/Euratom Council Directive, are based on the annual average of indoor radon concentration, assuming it is representative of the long-term average. However, a single annual radon concentration measurement does not reflect annual variations (i.e. year-to-year variations) of radon concentration in the same location. These variations, if not negligible, should be considered for an optimized implementation of regulations. Unfortunately, studies on annual variations in workplaces can be difficult and time-consuming and no data have been published on scientific journals on this issue. Therefore, we carried out a study to obtain a first evaluation of short-term annual variations in workplaces of a research institute in Rome (Italy). The radon concentration was measured in 120 rooms (mainly offices and laboratories) located in 23 buildings. In each room, two 1-year long measurements were performed, with an interval between the two measurements of up to 3 years. The results show variability between the two 1-year long measurements higher than the variability observed in a sample of dwellings in the same area. Further studies are required to confirm the results and to extend the study to other types of workplaces.